Vitamin D serum level as a prognostic factor in 1 predicting mortality severe COVID-19 patients: An evidence based case report - Heny Puspita; Marcia Kumala; Yohannessa Wulandari (Indonesian Nutrition Association, 2022)
Introduction: The mortality rate of COVID-19 is still high. Many prognostic factors have been studied to decrease the mortality rate. One of the many factors is vitamin D status, known for years as an immunomodulator and anti-inflammatory agent. Vitamin D deficiency could worsen the symptoms of COVID-19 and ultimately lead to mortality. However, some literature shows controversial results. Methods: Literature research was conducted by advanced searching in Pubmed, Cochrane Library, Scopus, and ProQuest, using a combination of both MeSH Terms and Title/Abstract. After removing duplicates, these literature were screened according to the eligibility criteria. Appraisal and level of evidence of the final literature were determined based on Oxford Centre for Evidence-Based Medicine. Results: Two selected literature were relevant to answer our clinical question. The former is a retrospective cohort study by Radujkovic et al. (2020), while the latter is a prospective cohort study by Bennouar et al. (2020). Both show similar results that low vitamin D serum levels in severe COVID-19 patients can increase the in-hospital mortality risk. Conclusion: Vitamin D is one of the prognostic factors that can predict the mortality rate of severe COVID-19 patients. We suggest that vitamin D serum level can be measured regularly in COVID-19 patients and administered to patients with such deficiencies. Adequate vitamin D deficiency management is expected to lower the COVID-19 mortality rate.